What Dewey Knew. The Public as Problem, Practice, and Art - Laura Bieger (European Journal of American Studies)
This essay takes the present “post truth” threat to democratic politics as an occasion to revisit John Dewey’s view of the public as a political actor that is both indispensible for the project of modern democracy and vulnerable to self-effacement. Drawing on a recent development in democratic theory—epistemic democracy—that is in part inspired by Dewey, I trace how Dewey’s relativist understanding of truth animates his views of the public as a political actor and of democracy as a “collective exercise in practical intelligence” (Festenstein). But in linking the epistemic thrust of Dewey’s political theory with his view of communication as art, I move beyond established understandings of epistemic democracy to argue that the aesthetic is assigned with a key role in collectively exercising the practical intelligence that both sustains democracy and moves it forward—and that epistemic democrats have overlooked so far.